Bilateral Traumatic Globe Luxation with Optic Nerve Transection - Levent Tok; Ozlem Yalcin Tok; Tugba Cakmak Argun; Omer Yilmaz; Alime Gunes; Elif Nisa Unlu; Sezgin Sezer; Seda Ibisoglu; Mehmet Argun (Case Reports in Ophthalmology, 2014)
Purpose: The purpose of this study was to document clinical findings and management of a patient with bilateral globe luxation and optic nerve transection. Materials and Methods: A 25-year-old female patient was admitted to the emergency department with bilateral traumatic globe luxation following a motor vehicle accident. Results: Visual acuity testing showed no light perception. The right pupil was dilated and bilaterally did not react to light. The globes were bilaterally intact. A computed tomography scan revealed Le Fort type II fractures, bilateral optic nerve transection and disruption of all extraocular muscles. The globes of the patient were bilaterally reduced into the orbit. However, the patient developed phthisis bulbi in the right eye at month 3. Conclusion: Globe luxation presents a dramatic clinical picture, and may lead to the development of severe complications due to the concomitance of complete optic nerve dissection and multiple traumas. Even if the luxated globe is repositioned into the orbit, there is still an increased risk of the development of phthisis due to ischemia.